Linking the early development instrument with the ICF-CY. (1st January 2018) - Castro, Susana; Grande, Catarina
Abstract : Objective : The International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY) provides a universal taxonomy to describe functioning. One of the most relevant applications of the ICF has been the development of code-sets for particular contexts/situations, such specific age groups. An important step in research around child assessment and intervention is to identify extant measures that can assess the essential functioning features for each age range. This study aims to map the Early Development Instrument (EDI) with the ICF-CY and to identify the functioning dimensions regarded by experts as essential in the age range 3–5 that are covered by this instrument. Method : A systematic deductive content analysis procedure was used in the mapping process. Results : Most of EDI items were mapped to Activities and Participation and the majority of Activities and Participation regarded as essential from 3 to 5 years are assessed by the EDI; only some essential Environmental Factors and Body Functions are covered. Conclusion : The mapping process between the EDI and the ICF has shown that the EDI should be complemented with other measures with a focus on Body Functions and Environmental Factors, in order to facilitate a holistic description of the child.